An Exploratory Analysis of Collective Patterns of Conscious Experience Using a Self-Report Questionnaire - Brazdau, Ovidiu; Ahuja, Sona; Opariuc, Cristian-Dan; Jones, Valita; Sharma, Sadhna; Monsanto, Carlo; Andrews, Sperry; Fiveson, Keith (Frontiers in Psychology, 2021)
This study is an exploration of collective patterns of conscious experience, as described by various psychological models, using a self-report questionnaire: The Consciousness Quotient Inventory (CQ-i). The CQ-i evaluates patterns of behaviors, attitudes, and attentional styles as well as the usage of conscious skills, awareness, and the capacity to “feel awake and alive,” providing a complex exploration of conscious experience. A set of 237 items covering major aspects of the subjective conscious experience was selected to detect the phenomenal patterns of subjective conscious experience. An exploratory factor analysis on a large sample (N = 2,360), combined with our previous meta-research on conceptual convergence of conscious experiences, revealed that these experiences appear to have 15 patterns common to all of us. A sample with a quasi-normal distribution (n = 2,266) was employed for standardization and classification of scores (M = 100; SD = 15). The study provides a conceptual framework for future in-depth studies on collective patterns of self-awareness, inner growth dynamics, and psychological maturity.